Główne nurty w badaniach nad filmem i religią - Domalewski , Adam (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article is a meta-study and provides an original typology of research on film and religion, based on Polish and English academic sources. The author proposes to divide this field of research into four main domains, which he names successively: substantial-theological, anthropological-mythological, socio-cultural and post-secular. The following descriptive criteria were used to introduce this division: the relationship between religion and culture adopted (usually implicitly) in a given direction of research, the concept of both human and religion emerging from them, and the established subject and scope of research, as well as the basic set of tools used within them. The proposed systematic is intended to help capture the significant differences between the main types of research on film and religion, both in terms of research assumptions, methods of analysis, and set goals.